Teacher Performance Evaluation: A Study of Discipline, Creativity, and Cooperation in the Learning Process - Assya'bani, Ridhatullah; Huda, Nurul; Hermina, Dina (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to evaluate the performance of teachers at Tahfidz Nurul Musthofa Junior High School through a study of discipline, creativity, and cooperation in the learning process. The evaluation model used is CIPP (Context, Input, Process, Product), which allows a comprehensive analysis of the four main components in teacher performance evaluation. This study adopts a qualitative approach with a case study method, where data is collected through interviews, observations, and documentation. The results of the study show that from the aspect of discipline, most teachers have shown a high commitment in maintaining discipline both in time management and classroom management. However, there are some challenges in ensuring consistent discipline among students. In terms of creativity, teachers at this school have made efforts to implement varied and innovative learning methods, although there is still a need for improvement in the use of educational technology. The cooperative aspect is also a strength in this school, with teachers actively collaborating in designing learning materials and supporting student development. Through the evaluation of CIPP, this study provides recommendations to improve professional training for teachers, as well as further development in the use of technology in learning. This research is expected to contribute to improving teacher performance and improving the quality of learning at Tahfidz Nurul Mustofa Junior High School.